Proceedings of the 3rd Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2018) 2018
DOI: 10.2991/aisteel-18.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visual Mapping and Science-Related Attitudes on Students’ Problem Solving Skills

Abstract: The aims of this study were to find out: (1) the effects of visual mapping on students' problem solving skills, (2) the effects of science-related attitudes on students' problem solving skills, and (3) the interactions between visual mapping and science-related attitudes on students' problem solving skills. This study was conducted at MAN 1 Tanjung Pura, with the samples of 141 students of XI-Science Program. This study was a quasi-experimental technique by using a pretest-posttest experimental group with 4x2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Meanwhile, there is a researcher developing new learning model to enhance student's problem-solving skills [31]. Visual mapping also can be one of solution to improve students' problem-solving skills [32]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there is a researcher developing new learning model to enhance student's problem-solving skills [31]. Visual mapping also can be one of solution to improve students' problem-solving skills [32]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive processes in problem solving are directed at solving a problem. Problem solving includes higher order thinking skills (Jamhari et al, 2018). To solve problems, students need to think critically, be scientifically, and formulate coherent evidence-based arguments.…”
Section: Problem Based Learning (Pbl)mentioning
confidence: 99%
“…The main findings of the study indicated that students in the experimental group taught through activity with low-cost materials showed significantly greater attitude towards science (Chemistry) than the control group. Jamhari and Sipahutar (2018) studied the effects of science-related attitudes on students' problem-solving skills, and the interactions between the visual mapping and science-related attitudes on students' problem-solving skills. This study was conducted at MAN TanjungPura, with the samples of 141 students of the XI-Science Program.…”
Section: Introductionmentioning
confidence: 99%